Physiologically based pharmacokinetic modeling of long‐acting extended‐release naltrexone in pregnant women with opioid use disorder - Babajide Shenkoya; Mathangi Gopalakrishnan; Ahizechukwu C. Eke (Wiley, 2024)
Abstract Opioid use disorders (OUD) are a major issue in the U.S. Current treatments for pregnant women, like methadone and buprenorphine require daily dosing and have adverse effects. Monthly injectable naltrexone (XR‐NTX) mitigates these adverse effects but is not recommended during pregnancy due to limited pharmacokinetic and safety data. This study developed a physiologically based pharmacokinetic (PBPK) model to describe XR‐NTX pharmacokinetics during pregnancy, and to predict dosing recommendations. Model predictions were successfully validated with observed data. Maternal plasma XR‐NTX profiles were simulated for 400 non‐pregnant virtual females at the approved dose of 380 mg, then randomized to continue with either 380, 285, 190, or 95 mg during pregnancy. The non‐pregnant virtual females had a mean predicted Cmax, AUC0‐7days, and AUC0‐28days of 23.3 ng/mL, 142 ng·d/mL, and 148 ng·d/mL, respectively. Maternal XR‐NTX exposure (AUC0‐28days) were predicted to increase by 1.37, 1.43, and 1.72 times during the first, second, and third trimester of pregnancy. However, the fetal‐to‐maternal exposure (AUC0‐28days) was lower in the first (15%), second (7%), and third (9%) trimesters. A dose of 285 mg of XR‐NTX in pregnancy during the first/second trimester and dose of 190 mg in the third trimester were predicted to provide maternal exposures that were comparable to non‐pregnant levels at the standard dose. This study provides crucial insights into XR‐NTX pharmacokinetics and proposes a dosing strategy during pregnancy, potentially aiding further clinical investigations and decision making regarding XR‐NTX use during pregnancy.